(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study aims to assess the level of job satisfaction of the employees of public sector banks namely IOB, Indian bank, Canara bank and employees of private sector banks namely (ICICI, AXIS, and HDFC bank in Kanyakumari district. The population of the study consisted of all employees who are working in public sector banks namely IOB, Indian bank, Canara bank and employees of private sector banks namely ICICI, AXIS bank and HDFC bank in Kanyakumari district.